Uji Aktivitas Antibakteri Sediaan Sabun Cair Ekstrak Daun Mengkudu (Morinda citrifolia L.) Terhadap Staphylococcus aureus - Fajrin Noviyanto; Siti Nuriyah; Hadi Susilo (Journal Syifa Sciences and Clinical Research, 2020)
The bacteria Staphylococcus aureus are round bacteria that are shaped like a cocci, and are Gram-positive. These bacteria can be found on the skin, genitals, nasal cavity, mouth and around the anus. One of the pharmaceutical products that can maintain skin health and protect the skin is soap. The leaves of noni (M. citrifolia L.) contain various compounds such as flavonoids, tannins, saponins, alkaloids, and triterpenoids which are capable of being antibacterial. This study aims to make a liquid soap formulation from M. citrifolia L. leaf extract and its activity as an antibacterial to S aureus. The leaves of M. citrifolia L. were extracted using 96% ethanol solvent by maceration method until a thick extract was obtained. Soap formulations are made with a concentration of 20% 40% and 60%. Evaluation of soap quality includes organoleptic test, high foam test and pH test. The method of antibacterial testing is carried out in vitro by means of well diffusion. The results on the quality test of the liquid soap formulation showed that the pH and height of the foam had good results and had met the SNI 1996 Standards. From the results showed that formulation III with an extract content of 60% had a large antimicrobial activity with a value of 16.83 mm which was categorized as strong. In positive control (Dettol) 60% antimicrobial activity showed a value of 14.83 mm. The results of statistical tests were carried out by One-Way ANOVA analysis followed by LSD analysis Post hoc, liquid soap extract of M. citrifolia L. had greater antimicrobial potential than the positive control (Dettol).